2017
DOI: 10.1007/s00187-016-0244-3
|View full text |Cite
|
Sign up to set email alerts
|

Tensions at the intersection of management control and innovation: a literature review

Abstract: This paper reviews 47 articles dealing with tensions at the intersection of management control and innovation. One purpose is to present the status of the research in the area in terms of types of articles, research methods, theoretical approaches, and tension-related terms used. A second purpose is to conceptually compare the use and interpretations of tension in the reviewed articles, as well as to systematically map and categorize highlighted competing demands. A third purpose is to suggest a tension-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(78 citation statements)
references
References 82 publications
(145 reference statements)
4
63
0
Order By: Relevance
“…It has been widely used to study the problems of managing creativity and innovations (cf. Bisbe and Otley 2004;Henri 2006;Malagueño 2009, 2015;Mundy 2010;Bedford 2015;Curtis and Sweeney 2017), mainly through the interactive and diagnostic use of management control systems (Lövstål and Jontoft 2017). Simons (1987) defines management control systems as formalized procedures and systems that use information to maintain or change patterns in organizational activity.…”
Section: Levers Of Control Frameworkmentioning
confidence: 99%
“…It has been widely used to study the problems of managing creativity and innovations (cf. Bisbe and Otley 2004;Henri 2006;Malagueño 2009, 2015;Mundy 2010;Bedford 2015;Curtis and Sweeney 2017), mainly through the interactive and diagnostic use of management control systems (Lövstål and Jontoft 2017). Simons (1987) defines management control systems as formalized procedures and systems that use information to maintain or change patterns in organizational activity.…”
Section: Levers Of Control Frameworkmentioning
confidence: 99%
“…This research responds to calls for accounting research on the practitioners' perspective (e.g. Chua 2007;Jönsson 1998;Gerdin et al 2014;Hall 2010;Lövstål and Jontoft 2017) and to study control and innovation on a more specific level than that of the organization (Davila et al 2009;Tervala et al 2017;Chenhall and Moers 2015;Davila et al 2009), with a focus instead on subjective mechanisms and informal systems of control (Reimer et al 2016;Tervala et al 2017;Martyn et al 2016). The results suggest that, from the perspective of an individual manager, strategic thinking is much more than straightforward analytical decision-making and the role of accounting is wide-ranging.…”
Section: Theoretical Contributionmentioning
confidence: 66%
“…Furthermore, it has been found that the perception of coercive and enabling form of control can change over time (Jordan and Messner 2012) and coexist simultaneously (Adler 2012). This study approaches the dual nature of accounting recognized in the previous literature by adopting a practice-oriented approach (Lövstål and Jontoft 2017), examining the tensions that managers confront specifically in their strategic thinking. The research question of this study is as follows: What are the ways in which experienced managers find accounting useful in strategic thinking and what are the disadvantages they have experienced?…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations